Comparative performance of common grain legumes in the Sudan savanna zone of Nigeria - Ajeigbe, Hakeem A.; Kamara, A.; Chikoye, David (2008)
A trial was conducted in minjibir in the sudan savanna zone of Nigeria to evaluate the performance of common grain leguminous crops in the area. Significant differences are found among and within the grain legumes for days to flowering, maturity and ripening. Cowpea had significantly fewer days to flowering, ripening and maturity compared to other legumes. It also has significantly higher threshing % and harvest index. Soybean and cowpea produced significantly higher grain yield than groundnut and bambara nut, while groundnut and soybean produced significantly higher fodder than cowpea and bambara nut. Significant differences were found among and with the grain legumes for days to flowering, maturity and ripening.